Hand Sanitizer With Eucalyptus Scent For The Community As A Contribution To Dealing With Pandemic Conditions: A Community Service Report - Rini; Kesuma, Sayuti; Eddwina Aidila, Fitria (Andalasian International Journal of Social and Entrepreneurial Development, 2021)
Background: This activity was carried out to participate in preventing the spread of the COVID 19virus in the city of Padang, West Sumatera Province. Methodology: The hand sanitizer was producedindependently and was distribute to the public society in Padang City for period of November 2020.Conclusion: The distribution of eucalyptus flavored hand sanitizers provided another variant of existinghand sanitizer. The distinctive aroma of eucalyptus flavored hand sanitizers is very popular with thecommunity and is expected to increase their awareness of using hand sanitizers to maintain their sanitationduring the new normal in the current COVID 19 pandemic era.